Challenges faced by female graduate students working in the private sector - Al-Hammad, Raya Abdullah; Al-Shehri, Fatima Jaber; Al-Shammari, Ohood Saud; Al-Saqri, Awatif Ibrahim (Journal of Educational and Psychological Sciences, 2024)
The students of the Faculty of graduate studies are faced with several pressures and scientific, academic, administrative and financial problems that limit the researcher’s activity and hinder his performance, reduce the quality of his work, hinder his development and progress, or lead to atrophy of his desire to complete his doctoral study, or may cause him to drop out of the master’s or doctoral program; so this research came, which aimed to identify the physical challenges, psychological challenges, and academic challenges facing graduate students working in the private sector, using the qualitative method (case study), using the interview tool, and then analyzing it qualitatively with the category the most notable results on the physical challenges were: 1- The high price of paid programs, 2- And the high value of books and References, 3-and the high cost of transportation and services, 4-and the high cost of Housing and living, as for the psychological challenges centered on 1-feeling exhausted most of the time, 2-and fear of failure in Study, 3-and the lack of consideration of the teaching staff for the conditions of students, and the last question about the academic challenges came to 1- insufficient knowledge of the methods of scientific publication of research, 2-and the poor level of English, 3-and the difficulty of choosing the title of the thesis, 4-and the lack of compatibility between the student and the academic supervisor, 5- and the high cost of materials, this research came out with several recommendations, including: Universities and governments should provide the necessary support to higher education students, raise the level of quality of education and research, encourage the facilitation of funding for study, take into account people with limited incomes, and provide extensive advisory services.